SYNTHESIS AND CHARACTERIZATION OF AZO CONJUGATES OF FENOPROFEN FOR TREATMENT OF INFLAMMATORY BOWEL DISEASE THROUGH COLON TARGETING - Jain, Poorva; Jain, Nivrati; Jain, Prateek Kumar (International Journal of Current Pharmaceutical Research, 2015)
Objective: The objective of this research was to synthesize azo conjugates of fenoprofen (FP) for treatment of inflammatory bowel disease through colon targeting. Methods: Six prodrugs of FP were synthesized by diazotisation with ethyl esters of amino acids, namely, glycine, tyrosine L-phenylalanine, L-tryptophan, L-valine, L-alanine, amino acid. Methyl ester hydrochloride prepared by thionyl chloride, methanol and amino acids, followed by diazotization and then Coupling of diazotized amino acid methyl ester with fenoprofen. Six azo prodrug of fenoprofen was synthesized by using amino acid. Further, the synthesized prodrugs were characterized by TLC, IR, NMR spectroscopic analysis and subjected to in vitro drug release, TNBS induced ulcerative colitis and ulcerogenic index. Results: All synthesized prodrugs showed excellent pharmacological response and targeting to colon. The FTIR and NMR study confirmed the structure of all azo linkage prodrugs. In vitro drug release studies revealed that FP was not release in gastric fluid. 12-15% drug were released in intestinal fluid and 65-85% drug was released in the colon because of azo reductases enzyme, secreted by colonic microflora. The azo prodrugs proved their potential in reducing the inflammation proved by the histopathology of the resected colon from every group of animals. Conclusion: The results obtained in this research work clearly indicated a promising potential for treatment of inflammatory bowel disease through colon targeting for the effective treatment of IBD.